An argument for infrastructure system stewardship: A New Zealand transportation case study in benefit management - Blom, C; Guthrie, P (International Information and Engineering Technology Association, 2017)
Benefits are intrinsic to infrastructure and the public sector, yet these remain a problem for many infrastructure sectors (including transportation), organisations, and countries. Much of the focus upon benefit management targets project delivery; by contrast, this study considers system-level benefit management using a transportation case study from New Zealand. In so doing, it investigates why the matter of benefits might be so problematic, and in what way this might affect the integration of projects into the extant system. The research shows system-level co-ordination and integration are being lost within the ‘tactical strategy’ of programmes and initiatives. In turn, this is creating a ‘red queen’-like busyness without a real understanding of whether anything has been achieved relative to the intended or necessary outcomes being sought. System stewardship has therefore been advanced as an appropriate response to system-level complexity and a potential enabler of strategic agility and adaptive capacity.
Keywords: transportation; system thinking; benefit realisation; stewardship; integration